COMPARISON OF LEARNING MATH LEARNING RESULT STUDENTS WITH SAVI MODEL AND NHT MODEL ON STUDENT SMKN 1 KOLAKA - S. Supratman; Sri Wulandari Muhlis (Universitas Sembilanbelas November Kolaka, 2018)
The formulation of the problem in this research are: (1) How the result of learning mathematics of students after taught by SAVI learning model?, (2) How the result of learning mathematics of students after taught by NHT learning model?, (3) Is the result of learning mathematics of students who taught with SAVI learning model is higher than students taught by NHT learning model. The purpose of this study are: (1) To know how the results of learning mathematics students after teaching with SAVI learning model, (2) To find out how the results of learning mathematics students after being taught with NHT learning model, (3) To determine whether the results of learning mathematics students taught by SAVI learning models higher than students taught by NHT learning models. Type of research using experimental method. The population in this study is all students of class X spread in 11 parallel classes with the number of 310 people. Sampling was done by using cluster random sampling technique. In this research as a sample taken 2 classes from the entire population that is class X A3 as experiment class 1 using SAVI learning model and class X A1 as experiment class 2 using NHT learning model. From result of data analysis obtained that: (1) result of student learning taught by using SAVI learning model which consist of 25 students show minimum value 62, maximum value 96, mean (mean) 80,36, with standard deviation 9,10; (2) student learning outcomes taught using NHT learning model consisting of 25 students showing minimum score 62, maximum value 96, mean (mean) 79,62, with standard deviation 10,512; (3) result of t-test analysis using independent sample t-test obtained tcount = 0,302 at = 0,05 with degrees of freedom (dk) = 48 obtained t table = 2,011. Because t t table then Ha is rejected and H0 is accepted. So it can be concluded that the mathematics learning outcomes of students who were taught with the SAVI model was not higher than the students taught by the NHT model.